EFFECTS OF CR, DAR, TAT AND ROA ON CONSUMER INDUSTRY GROWTH AND CORPORATE PROFITS - Jennisa Dwina Indriani; Muhammad Ihsan (Jurnal Ipteks Terapan : research of applied science and education, 2023)
This study aims to determine the impact of the variables current ratio, debt ratio, total asset turnover and ROA on profit growth. The object of this study was 53 companies selected according to the purposive sampling method with certain criteria, amounting to 25 companies. The type of data used in this study is quantitative data. The data source in this study is secondary data. Data collection techniques were performed using linear analytical data analysis and documentation techniques. The research results partly show that current ratio has a negative and significant impact on profit growth, while debt ratio, total asset turnover and ROA do not have a significant impact on growth. profit. The research results also show that the current ratio, debt ratio, total asset turnover and ROA are related to earnings growth